Investigation of Pressure Distributions for a Finite Elasto-Hydrodynamic Journal Bearing Lubricated by Ferro Fluids with Couple Stresses - Kihuga, D; Kimathi, M; Kinyanjui, M (My University, 2014)
The performance of finite elastohydrodynamic journal bearings lubricated by ferrofluids with couple stresses has been studied. We derive a Reynolds equation that takes into account magneto elastohydrodynamics, by using the continuity and momentum equations. The equation has been integrated locally across the film thickness and an equation for the pressure gradient obtained as a function of film thickness and total mass flow rate of lubricant, the modified Reynolds equation. The modified Reynolds equation obtained is solved numerically by the finite difference technique since it is highly non-linear. The numerical scheme used is implemented in MATLAB so as to obtain the approximate solutions. The pressure distributions are obtained and the solutions obtained represented in graphs. It is clear from the results that the pressure increases with the increase in magnetism and the couple stress.
Keywords: Journal Bearing; Reynolds Equation; Magneto-Elasto-Hydrodynamic Lubrication; Couple Stresses